(untitled) (Principles and Practice of Clinical Research, 2022)
Introduction: The Coronavirus Disease 2019 (COVID-19) pandemic has hit globally, both economically and in the collective health, leaving irreparable human losses. In addition to preventive measures such as the use of masks and physical distancing to mitigate the ravages of the pandemic, the method of immunization through vaccines has been applied, the health cabinet of the Dominican Republic (DR) began with the national vaccination campaign against COVID-19 “Vacúnate RD”, to establish a quicker herd immunity and thus reduce morbidity and mortality. Objective: To determine the acceptance of the population regarding the vaccination process and the proposal of a third dose by the Public Health authorities in the DR. Methods: A descriptive, prospective, cross-sectional study, carried out in a 10-day collection period, which consisted of an online survey with 20 questions, divided into 3 sections and written in Spanish, the official language of the country. Results: With a total of 1096 valid answers for the statistical analysis, regarding the immunization schedule, 55.9% consider that it should not be mandatory. At the time of the survey, 6.7% had not been applied any dose from the vaccine, 7.6% had the first dose, 81.9% (n=898) had completed their scheme with the second dose, and 41 participants reported having received the third dose; the most applied vaccines among those surveyed were Sinovac (68.2%, n=747), AstraZeneca (19.6%, n=215) and Pfizer (3.8%, n=42). 41.1% (n=451) responded affirmatively to the idea of an eventual application of a third dose vaccine, while 31.5% do not feel safe to apply said, "booster dose" and 27.4% responded negatively to this idea. Conclusion: In general, an acceptance was observed in the study population of getting the vaccine against COVID-19, trusting its protective effects, although there is still a high percentage of people who expressed doubts regarding the idea proposed by the health authorities in the DR about completing the third dose as a reinforcement of the immunization scheme already established worldwide by the relevant health organizations.